The force unleashed - Williams, Sean, 1967- (Star wars. Legends., 2024)
“The Sith always betray one another. . . . I’m sure you’ll learn that soon enough.” The overthrow of the Republic is complete. Absolute power now rests in the iron fist of Darth Sidious–the cunning Sith Lord better known as Emperor Palpatine.But more remains to be done. Pockets of resistance in the galaxy must still be defeated and missing Jedi accounted for . . . and dealt with. These crucial tasks fall to the Emperor’s ruthless enforcer, Darth Vader, who in turn has groomed a lethal, nameless Sith apprentice to secretly dispatch the last of his masters’ enemies. Since childhood, Vader’s nameless agent has known only the cold, mercenary creed of the Sith. His past is a void; his present, the carrying out of his deadly orders. But his future beckons like a glistening black jewel with the ultimate promise: to stand beside the only father he has ever known, with the galaxy at their feet. But there is one, in control of his master, that stands in the way. This acolyte’s journey will take him across the far reaches of the galaxy and test him with shattering revelations that strike at the very heart of all he believes, stirring within him long-forgotten hopes of reclaiming his name . . . and changing his destiny. --